SWOT ANALYSIS OF THE FOOD & BEVERAGE DEPARTMENT AT GRAND PRINCE HOTEL OSAKA BAY : CASE STUDY FROM AN OJT STUDENT PERSPECTIVE - Djody, Anissa Rizkya Utami; Adiatma, Dani; Dhamayanti, Stanny; Rukma, Deden Firman Syuyaman (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to analyze the factors of Strengths, Weaknesses, Opportunities, and Threats faced by the Food & Beverage (F&B) Department at the Grand Prince Hotel Osaka Bay. This analysis is based on the On-the-Job Training (OJT) experience of students of the Tourism Study Program at Garut University. Data were collected through direct observation and six months of work experience at the hotel. The results of this study indicate that the F&B Department has advantages in high-quality service, menu diversity, and a good internal communication system. However, several obstacles were found such as lack of manpower during peak times, difficulty in adapting for foreign workers, and relatively high menu prices for customers. Based on the SWOT analysis, this study provides strategic recommendations to improve the operational efficiency of the F&B Department at the Grand Prince Hotel Osaka Bay.